Performance Study of Load Flow Algorithms in Well and Ill-Conditioned Systems - Lea Tien Tay; Kai Seng Chieng (Institute of Advanced Engineering and Science, 2017)
Existing transmission systems are classified as either ill systems or healthy systems. Most of the load flow algorithms works proficiently under well-conditioned systems. However, some of those algorithms fail to produce the accurate results for ill-conditioned systems. This paper investigates the performance of eight load flow algorithms based on the conventional Newton-Raphson, Fast-decoupled and Second-order Load Flow methods for a wide range of electrical bus system sizes. Tests are carried out for each load flow algorithm on six different standard bus systems, each with five different ill-conditioning levels. The results show that improved load flow model with constant Jacobian has advantages over the conventional load flow approach in both well and ill-conditioned system, especially for large-scale system.